Evaluating the Effect of Extension Advisory Services (EAS) using Economic Index Score in Aspirational Districts - Ranjan, Amandeep; Satyapriya; Venu Lenin; Sitaram Bishnoi; Sukanya Barua; Mrinmoy Ray; Dinesh Kumar Sharma; Surjya Kanta Roy; P.N. Fatheen Abrar (Indian Journal of Extension Education, 2025)
The Aspirational Districts Programme (ADP) aims to uplift India’s most developmentally lagging regions through targeted interventions across health, education, agriculture, and infrastructure. The study evaluated the economic impact of EAS on farmers in four aspirational districts of Bihar and Jharkhand using a novel Economic Index Score (EIS) during 2024-25. The EIS was constructed using five key dimensions viz., employment generation, asset creation, agricultural productivity, cost reduction, and value addition, capturing both the presence and duration of economic benefits from EAS. The data were collected from 320 farmers and 30 service providers personally. The statistical analysis, including Welch’s ANOVA, Games-Howell post hoc tests, and Bayesian inference, revealed significant differences in EIS between beneficiary and non-beneficiary farmers, with a moderate to large effect size (Cohen’s d = 0.61). The district-wise comparisons also highlighted disparities, with Muzaffarpur showing the highest economic gains and Hazaribagh the lowest. The correlation analysis identified experience, mass media exposure, social participation, and extension contact as significant predictors of EIS. The findings established that EAS plays a crucial role in enhancing rural livelihoods, yet variations across districts and farmer profiles underscore the need for context-specific, inclusive extension models.